2021
DOI: 10.1039/d0ra09976g
|View full text |Cite
|
Sign up to set email alerts
|

One-step preparation of eggplant-derived hierarchical porous graphitic biochar as efficient oxygen reduction catalyst in microbial fuel cells

Abstract: Eggplant-derived hierarchical porous graphitic biochar possessed good electrochemical performance as oxygen reduction reaction catalyst for microbial fuel cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(15 citation statements)
references
References 48 publications
0
14
0
Order By: Relevance
“…Although the maximal CD and PD of the CMFC with the AC electrode (control treatment) were 0.132±0.000 A/m 2 (16.500±0.001 A/m 3 ) and 0.007±0.000 W/m 2 (0.833±0.001 W/m 3 ) respectively. Single chamber MFC Water hyacinth 900 0.027 [25] Single chamber MFC Egg plant 800 0.667 [26] Stack MFC Corn cob 100-500 0.038 [27] Dual chamber MFC Rice straw 450 NA [28] Table 1. Comparison of biochar-based electrodes used in MFC.…”
Section: Resultsmentioning
confidence: 99%
“…Although the maximal CD and PD of the CMFC with the AC electrode (control treatment) were 0.132±0.000 A/m 2 (16.500±0.001 A/m 3 ) and 0.007±0.000 W/m 2 (0.833±0.001 W/m 3 ) respectively. Single chamber MFC Water hyacinth 900 0.027 [25] Single chamber MFC Egg plant 800 0.667 [26] Stack MFC Corn cob 100-500 0.038 [27] Dual chamber MFC Rice straw 450 NA [28] Table 1. Comparison of biochar-based electrodes used in MFC.…”
Section: Resultsmentioning
confidence: 99%
“…The formation of the pore structure of the material mainly utilizes the following mechanisms, as shown in eqn (3)- (8). First, K 2 FeO 4 starts to react and be decomposed at 300 °C to form Fe(OH) 3 , KOH, Fe 2 O 3 , and K 2 O.…”
Section: Materials Characterizationmentioning
confidence: 99%
“…Furthermore, MSAC-750 has the highest content of pyridine-N and Fe-N X , which allows for more active sites of the ORR. 8 As shown in Fig. 6(a), the Tafel curve can also be used to study the catalytic performance of different MSAC catalysts.…”
Section: Electrochemical Activitymentioning
confidence: 99%
“…Many studies have recently shown the applicability of biochars as anodes, cathodes, and semipermeable membrane materials in MFCs [7,[22][23][24][25][26][27]. Biochars are complex, heterogeneous materials consisting of mineral phases, amorphous carbon, graphitic carbon, and labile organic molecules, many of which can be either electron donors or acceptors [7,24].…”
Section: Biochar: a Promising Electrode Materialsmentioning
confidence: 99%
“…Many studies have recently shown the applicability of biochars as anodes, cathodes, and semipermeable membrane materials in MFCs [7,[22][23][24][25][26][27]. Biochars are complex, heterogeneous materials consisting of mineral phases, amorphous carbon, graphitic carbon, and labile organic molecules, many of which can be either electron donors or acceptors [7,24]. Joseph et al reported in [28] that nanoparticles with redox-active Fe-and Mn-based minerals, usually present in high-temperature biochars, play an important role in mediating the direct electronic transfer (DET) among bacteria (such as Geobacter spp and Shewanella oneidensis) and the anode.…”
Section: Biochar: a Promising Electrode Materialsmentioning
confidence: 99%